ANALISIS PENGARUH ARTIFICIAL INTELLIGENCE (AI) DAN KOMPETENSI DOSEN TERHADAP PROSES PEMBELAJARAN - Rini Mustika; Islamuddin Islamuddin (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) and Lecturer Competence on the Learning Process of Students at the Faculty of Economics and Business, Muhammadiyah University of Bengkulu. This research is quantitative. The population of this study was 1,054 active students at the Faculty of Economics and Business. The sampling technique used was Proportionate Stratified Random Sampling, meaning the total sample for each class was determined proportionally. Therefore, the sample size for this study was 200 students. Based on the t-test, the calculated t-value for the Artificial Intelligence (AI) variable was 3.777, which was greater than the t-table value of 1.960, with a t-probability of 0.000, which is less than the significance limit of 0.05. Based on the test results, the Artificial Intelligence (AI) variable has a positive and significant effect on the learning process. For the Lecturer Competence variable, the calculated value is 4.493, which is greater than the t-table value of 1.960, with a t-probability of 0.000, which is less than the significance limit of 0.05. Based on these test results, the lecturer competency variable has a positive and significant effect on the learning process. Based on the F-test results, the calculated F-value is 56.107, which is greater than the F-table value of 2.65, with a sig value of 0.000, which is less than 0.05. This indicates that Ho is rejected and Ha is accepted. This means that Artificial Intelligence (AI) and Lecturer Competence simultaneously have a positive and simultaneous effect on the learning process variable. Keywords: Artificial Intelligence (AI), Lecturer Competence, and Learning Process